A cross-sectional descriptive study assessing minimum dietary diversity among women desiring pregnancy in tribal and non-tribal blocks in rural area of a north Maharashtra district, India - Doke, Prakash Prabhakarrao; Chutke, Amruta P; Palkar, Sonali H (Indian Journal of Community Health, 2025)
Introduction: Minimum Dietary Diversity reflects the consumption of micronutrients and is measured by assessing consumption items from various food groups. The preconception phase is crucial in women’s reproductive cycle. Objectives: to estimate the proportion of women having minimum dietary diversity in desiring to conceive within one year in tribal and non-trial blocks, to compare the proportion in tribal and non-tribal blocks, and to identify associated risk factors. Methods: A cross-sectional descriptive study of two tribal and two non-tribal blocks in the Nashik district of Maharashtra. All women desiring pregnancy in a year were enrolled. The consumed items in 24 hours were grouped into ten. The study gave one score for each consumed group. The study considered accomplished minimum dietary diversity when the woman scored five or more. Results: The study enrolled 7,794 women. The mean age of the women was 23.19 years (SD=3.72). The mean dietary diversity score of the women was 4.73 (SD=0.7), 68.8% had minimum dietary diversity, and there was no difference between tribal and non-tribal blocks. Starchy food consumption was 100%, and fruit and vegetable consumption were minimal. Lower parity had a positive effect (AOR =0.90; CI 95%= 0.81-0.99). Unemployed women (AOR =1.12; CI 95% =1.01-1.24), consumption of tobacco in any form (AOR=1.38; CI 95% =1.11-1.70), and substantially less protein intake (AOR=2.49; CI 95%=1.61-3.84) had a negative effect. Conclusions: About two-thirds of women had minimum dietary diversity. Residence in tribal areas did not affect, but socio-demographic factors, tobacco, and less protein consumption affected minimum dietary diversity.